In Vitro Activity of β-Lactams in Combination with β-Lactamase Inhibitors against Multidrug-Resistant Mycobacterium tuberculosis Isolates - Zhang, Dan (Antimicrob Agents Chemother, 2015)
The combination of β-lactams and β-lactamase inhibitors has been shown to have potent in vitro activity against multidrug-resistant tuberculosis (MDR-TB) isolates. In order to identify the most potent β-lactam–β-lactamase inhibitor combination against MDR-TB, we selected nine β-lactams and three β-lactamase inhibitors, which belong to different subgroups. A total of 121 MDR-TB strains were included in this study. Out of the β-lactams used herein, biapenem was the most effective against MDR-TB and had an MIC(50) value of 8 μg/ml. However, after the addition of clavulanate or sulbactam, meropenem exhibited the most potent anti-MDR-TB activity with an MIC(50) value of 4 μg/ml. For meropenem, 76 (62.8%), 41 (33.9%), and 22 (18.2%) of the 121 MDR-TB strains were subjected to a synergistic effect when the drug was combined with sulbactam, tazobactam, or clavulanate, respectively. Further statistical analysis revealed that significantly more strains experienced a synergistic effect when exposed to the combination of meropenem with sulbactam than when exposed to meropenem in combination with tazobactam or clavulanate, respectively (P < 0.01). In addition, a total of 10.7% (13/121) of isolates harbored mutations in the blaC gene, with two different nucleotide substitutions: AGT333AGG and ATC786ATT. For the strains with a Ser111Arg substitution in BlaC, a better synergistic effect was observed in the meropenem-clavulanate and in the amoxicillin-clavulanate combinations than that in a synonymous single nucleotide polymorphism (SNP) group. In conclusion, our findings demonstrate that the combination of meropenem and sulbactam shows the most potent activity against MDR-TB isolates. In addition, the Ser111Arg substitution of BlaC may be associated with an increased susceptibility of MDR-TB isolates to meropenem and amoxicillin in the presence of clavulanate.